Segment coupling and coordination variability analyses of the roundhouse kick in taekwondo relative to the initial stance position - Estevan, Isaac; Freedman Silvernail, Julia; Jandacka, Daniel; Falco, Coral (Journal of sports sciences, 2016)
The initial stance position (ISP) has been observed as a factor affecting the execution technique during taekwondo kicks. In the present study, authors aimed to analyse a roundhouse kick to the chest by measuring movement coordination and the variability of coordination and comparing this across the different ISP (0°, 45° and 90°). Eight experienced taekwondo athletes performed consecutive kicking trials in random order from every of the three relative positions. The execution was divided into three phases (stance, first swing and second swing phase). A motion capture system was used to measure athletes' angular displacement of pelvis and thigh. A modified vector coding technique was used to quantify the coordination of the segments which contributed to the overall movement. The variability of this coordination (CV) for each ISP was also calculated. Comparative analysis showed that during the stance phase in the transverse plane, athletes coordinated movement of the trunk and thigh with a higher frequency of in-phase and lower frequency of exclusive thigh rotation in the 0° stance than the 90° stance position (P < 0.05). CV was also influenced by the different ISP. During the first swing and the majority of the second swing phase, predominant in-phase coordination of the pelvis and thigh was observed. Including exercises that require in-phase movement could not only help athletes to acquire coordination stability but also efficiency. The existence of a constraint such as ISP implies an increase of the variability when the athletes have to kick from ISP they are not used to adopt (i.e., 0° and 90° ISP) as an evidence of adaptability in the athletes' execution technique.
Keywords: plnění a analýza úkolů; Motor Skills; dospělí; rotace; Movement; Female; variability; pohyb; Adult; Martial arts; ženské pohlaví; motorické dovednosti; Martial Arts; Thigh; Athletic Performance; lidé; postura těla; vector coding; Pelvis; biomechanika; Male; bojové sporty; Posture; stehno; pánev; sportovní výkon; Task Performance and Analysis; biomechanics; mužské pohlaví; Rotation; dolní končetina; Lower Extremity; Biomechanical Phenomena; Humans